Digital Corporate Governance and Sustainability Reporting's Effect on Cash ETR and Firm Value - Antoro, Eko Wahyudi; Supriyadi, Stevanus Gatot; Harddian, Rahmad (Universitas Nusantara PGRI Kediri, 2024)
Research aim : The goal of this research is to investigate and assess the impact of digital corporate governance and sustainability reporting on cash ETR as a proxy for tax planning and business value, as well as cash ETR's effect on firm value. Design/Methode/Approach : This is a quantitative causal research approach. Secondary data was gathered from annual reports and other pertinent papers available on the Indonesian stock exchange's website. The population of this study is digital consumer goods companies that go public on the Indonesian stock exchange between 2017 and 2022, and the sampling technique used is purposive sampling with the criteria 1) consumer goods companies that always gain and do not lose between 2015 and 2019, and 2) to develop digital-based companies. This probe is centered on the corporation. The analytical technique used is path analysis. Research Finding : According to the study's findings, digital good corporate governance and sustainability reporting have a positive and significant impact on Cash ETR and firm value. Then there's Cash ETR, which has a significant and favorable firm value. Theoretical contribution/Originality : In order to better comprehend corporate governance elements, this research studies two theories: agency theory, which investigates the agent-principal relationship, and information asymmetry theory, which examines the inequality in knowledge possessed by individuals or parties. The former originated as a result of contemporary enterprises' separation of corporate ownership and management, whilst the latter focuses on capital market data analysis. Practitionel/Policy implication : Tax planning is especially critical for consumer products firms at this time, as many are growing into the internet industry. Because the firm must effectively manage the income shared between the holding company and the company, as well as its tax obligations. As a result, these businesses must have strong governance. Research limitation : Only consumer goods firms that have implemented digital corporate governance and digital-based sustainability reporting were studied in this study.